PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 15 PANGKALAN NYIRIH - Justia Justia; Lazim N Lazim N; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low of science learning result of fourth grade students of SD Negeri 15 Pangkalan Nyirih with average value 62,88 (KKM 70). Of the 26 students only 10 students (38.46%) reached the KKM, and the remaining 16 students (61.54%) did not reach the KKM. The purpose of this research is to improve the science learning outcomes of fourth grade students of SD Negeri 15 Pangkalan Nyirih, with the application of Inquiry learning model. Teacher activity increased, in the first meeting of the I-cycle of teacher activity average 79.16% with the category of